SCREENING OF BRASSICA GERMPLASM FOR RESISTANCE TO MAJOR DISEASES OF RAPESEED-MUSTARD - K. S. BISHT, MEENAKSHI RANA, KALPANA GAIROLA, B. C. SHARMA, A. K. TEWARI R. P. AWASTHI (The Bioscan, 2015)
In the present investigation 240 Brassica germplasm were screened in infested field against major disease of rapeseed-mustard (Brassica sp.). Out of 240 Brassica germplasm only seven viz. IC-255498, IC-296685, IC- 326253, IC-335847, IC-339589, IC-339597 and IC-417020 were found to be multiple disease resistant with 5- 25% disease severity against aforesaid diseases except IC-296685, IC-399678 and IC-401570 which showed 0% disease severity against white rust disease whereas IC-296685 showed 0% disease severity against downy mildew disease. The resistant sources will be useful for selecting elite genotypes for disease resistant where rapeseed- mustard is prevalent. In addition, the resistant genotypes can serve as a gene pool used in breeding programmes to develop new resistant genotypes.